Effect of Microbial Fuel Cell, fertilizer, and plant spacing on nitrogen dynamics in paddy soil - Efendi, Syahrul; Komariah, Komariah; Syamsiyah, Jauhari; Dewi, Widyatmani Sih; Hiramatsu, Ken; Azhar Fauzan, Adhia (Universitas Sebelas Maret, 2024)
Nitrogen is one of the primary nutrients required for growing rice. Still, the efficiency of urea fertilizer application is very low (20-40%) due to the nitrogen loss process, one of which is denitrification. This study aims to determine the effects of combining Microbial Fuel Cell (MFC), plant spacing, and fertilization on nitrogen dynamics in paddy fields. The combination of treatments are expected to reduce the nitrogen loss in paddy fields, and plants can absorb it efficiently. A total of six treatments included Microbial Fuel Cell (MFC) (2 levels: without MFC and with MFC), plant spacing (2 levels: conventional spacing 25 cm × 25 cm and jajar legowo spacing 25 cm × 12.5 cm × 50 cm), and fertilization (2 levels: without fertilizer and with 500 kg ha-1 of NPK fertilizer), with three replications for each combination. The observed parameters included total soil nitrogen, nitrate, nitrogen uptake, chlorophyll, nitrogen-fixing and denitrifying bacteria, and N2O gas emissions. The results showed that combining MFC, conventional spacing, and NPK fertilizer in the paddy fields resulted in a high total soil nitrogen (0.44%). The results showed different effects on total soil nitrogen in the MFC and fertilization treatments, leading to increased nitrate levels, nutrient uptake, and chlorophyll. Increasing total soil nitrogen significantly contributes to leaf development and significantly aids photosynthesis. The integration of MFC and fertilization observed in this study resulted in a real impact on nitrogen dynamics in paddy fields. This combined treatment effectively reduces total nitrogen loss due to denitrification in paddy fields, thereby increasing the efficiency of uptake by plants.